J/[psi] polarization in collisions at √s=7 TeV - Abelev, Betty; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Krawutschke, Tobias; Kweon, MinJung; Lohner, Daniel; Lu, Xianguo; Mercado Pérez, Jorge; Oyama, Ken; et al. (Physical review letters, 2012)
The ALICE Collaboration has studied J/ψ production in pp collisions at √s=7 TeV at the LHC through its muon pair decay. The polar and azimuthal angle distributions of the decay muons were measured, and results on the J/ψ polarization parameters λθ and λϕ were obtained. The study was performed in the kinematic region 2.5<y<4, 2<pt<8 GeV/c, in the helicity and Collins-Soper reference frames. In both frames, the polarization parameters are compatible with zero, within uncertainties.
B. Abelev, V. Anguelov, O. Busch, P. Glässel, R. Grajcarek, N. Herrmann, T. Krawutschke, M.J. Kweon, D. Lohner, X.-G. Lu, J. Mercado Pérez, K. Oyama, Y. Pachmayer, S. Radomski, K. Reygers, R. Schicker, K. Schweda, J. Stachel, J. Ulrich, S. Vallero, Y. Wang, J. Wiechula, A. Zimmermann [und weitere] (ALICE Collaboration)
Im Titel wird "psi" als griechischer Buchstabe dargestellt
Gesehen am 13.11.2018